3D graphene-containing structures for tissue engineering. (December 2019) - Li, J.; Liu, X.; Crook, J.M.; Wallace, G.G.
Abstract: Graphene and its derivatives have been extensively explored in various fields and have shown great promise toward energy harvesting, environmental protection, and health care. 3D graphene-containing structures (3DGCSs) are especially endowed with useable features relating to physicochemical properties within the hierarchical architectures. Thus, 3DGCSs are increasingly being applied for tissue engineering because of their supportability of human cells and functionalization potential. This review focuses on recent progress in tissue engineering utilizing 3DGCSs, providing insights into fabrication, application, and constraints in bionic research. Graphical abstract: Image 1